Chemical Regulation of the Protein Quality Control E3 Ubiquitin Ligase C‐Terminus of Hsc70 Interacting Protein (CHIP). (3rd February 2022) - Kanack, Adam J.; Olp, Michael D.; Newsom, Oliver J.; Scaglione, Jamie B.; Gooden, David M.; McMahon, Kevin; Smith, Brian C.; Scaglione, K. Matthew
Abstract: The ubiquitin ligase C‐terminus of Hsc70 interacting protein (CHIP) is an important regulator of proteostasis. Despite playing an important role in maintaining proteostasis, little progress has been made in developing small molecules that regulate ubiquitin transfer by CHIP. Here we used differential scanning fluorimetry to identify compounds that bound CHIP. Compounds that bound CHIP were then analyzed by quantitative ubiquitination assays to identify those that altered CHIP function. One compound, MS.001, inhibited both the chaperone binding and ubiquitin ligase activity of CHIP at low micromolar concentrations. Interestingly, we found that MS.001 did not have activity against isolated U‐box or tetratricopeptide (TPR) domains, but instead only inhibited full‐length CHIP. Using in silico docking we identified a potential MS.001 binding site on the linker domain of CHIP and mutation of this site rendered CHIP resistant to MS.001. Together our data identify an inhibitor of the E3 ligase CHIP and provides insight into the development of compounds that regulate CHIP activity. Abstract : Identification of a CHIP inhibitor : CHIP is a protein quality control E3 ubiquitin‐ligase that has been implicated in numerous diseases. Here we identified an inhibitor of CHIP and revealed that allosteric regulation of CHIP may be one way to regulate its activity.